2018
DOI: 10.3390/molecules23102613
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of 7-Hydroxycoumarin in Pseudomonas mandelii 7HK4 via ipso-Hydroxylation of 3-(2,4-Dihydroxyphenyl)-propionic Acid

Abstract: A gene cluster, denoted as hcdABC, required for the degradation of 3-(2,4-dihydroxyphenyl)-propionic acid has been cloned from 7-hydroxycoumarin-degrading Pseudomonas mandelii 7HK4 (DSM 107615), and sequenced. Bioinformatic analysis shows that the operon hcdABC encodes a flavin-binding hydroxylase (HcdA), an extradiol dioxygenase (HcdB), and a putative hydroxymuconic semialdehyde hydrolase (HcdC). The analysis of the recombinant HcdA activity in vitro confirms that this enzyme belongs to the group of ipso-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Hence, a hydrolysis in aqueous solutions takes place, resulting in the formation of 3-(2,4dihydroxyphenyl)propionic acid. Therefore, this work in combination with the previously published data [18] allow an elucidation of a pathway of catabolism of 7-hydroxycoumarin in Pseudomonas sp. 7HK4 bacteria (Figure 9).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Hence, a hydrolysis in aqueous solutions takes place, resulting in the formation of 3-(2,4dihydroxyphenyl)propionic acid. Therefore, this work in combination with the previously published data [18] allow an elucidation of a pathway of catabolism of 7-hydroxycoumarin in Pseudomonas sp. 7HK4 bacteria (Figure 9).…”
Section: Discussionmentioning
confidence: 74%
“…Thus, it was found that the transcription of the xenA38 gene was increased two-fold in the presence of 6-hydroxycoumarin and three-fold in the presence of 7-hydroxycoumarin. An expression of the xenA38 gene was also compared to the expression levels of hcdABC genes encoding a lower part of the degradation pathway of 7-hydroxycoumarin [18]. It was found that the levels of mRNA synthesis of hcdABC genes were increased 1000fold in the presence of 7-hydroxycoumarin ( Figure 3b).…”
Section: Quantitative Rt-pcr Analysis Of the Pseudomonas Mandelii 7hkmentioning
confidence: 99%
“…To optimize the growth conditions for each strain in BP medium, the effects of different temperature, pH value, and incubation time on growth conditions were investigated, respectively. Different incubation temperatures (25,30,35, and 40 • C) were tested for each strain and colony-forming units (CFUs) were counted following appropriate dilution of the cultures, plating them onto fresh BP agar medium and incubating for 48 h. Similarly, the effects of different pH values (5.0, 6.0, 7.0, 8.0, and 9.0) and incubation times (3, 5, 7, and 9 days) in BP medium were also tested for each strain.…”
Section: Optimization Of Bacterial Growth Conditionsmentioning
confidence: 99%
“…When different incubation times (3, 5, 7, and 9 d) were investigated, the colony numbers of all seven strains reached their maximum levels after 7 d incubation ( Figure 1B). In addition, we examined the effects of different incubation temperatures (25,30,35, and 40 • C) in BP medium. A 30 • C temperature was found to yield the most colony forming units for the majority of the strains ( Figure 1C), with the exception of BY6, which exhibited optimal growth at 25 • C. As shown in Figure 1D, BY1, BY2, and BY6 exhibited optimal growth at pH values around 6, whereas BY3, BY4, BY5, and BY7 yielded the most colony forming units at pH 7.…”
Section: Optimization Of Growth Conditions Of the Isolated Strains Inmentioning
confidence: 99%
See 1 more Smart Citation